2009
DOI: 10.1002/app.30754
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly(trimethylene terephthalate) nanocomposites incorporating multi‐walled carbon nanotubes

Abstract: Poly(trimethylene terephthalate) (PTT) nanocomposites containing multi-walled carbon nanotubes (MWNTs) were prepared using a melt-blending process. Acrylic acid-grafted PTT (PTT-g-AA) and multihydroxylfunctionalized MWNTs (MWNTsÀOH) were used to improve the compatibility and dispersibility of MWNTs within the PTT matrix. The nanocomposites were characterized morphologically by transmission electron microscopy and chemically using Fourier transform infrared absorbance, 13 C solid-state nuclear magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Initially, in-situ radical polymerization was applied for the synthesis of PMMA/MWCNT nanocomposites (Jia, 1999;Velasco-Santos, 2003;Putz, 2004). More recently (Wu, 2009) studied the mechanical and thermal properties of hydroxyl functionalized MWCNTs/acrylic acid grafted PTT nanocomposites and showed a significant enhancement in thermal and mechanical properties of PTT matrix due to the formation of ester bonds between -COOH groups of acrylic acid grafted PTT and -OH groups of MWCNTs. In-situ polymerization was also very useful for the preparation of polyamide/CNT polymer nanocomposites.…”
Section: Processing Of Cnt/polymer Nanocompositesmentioning
confidence: 99%
“…Initially, in-situ radical polymerization was applied for the synthesis of PMMA/MWCNT nanocomposites (Jia, 1999;Velasco-Santos, 2003;Putz, 2004). More recently (Wu, 2009) studied the mechanical and thermal properties of hydroxyl functionalized MWCNTs/acrylic acid grafted PTT nanocomposites and showed a significant enhancement in thermal and mechanical properties of PTT matrix due to the formation of ester bonds between -COOH groups of acrylic acid grafted PTT and -OH groups of MWCNTs. In-situ polymerization was also very useful for the preparation of polyamide/CNT polymer nanocomposites.…”
Section: Processing Of Cnt/polymer Nanocompositesmentioning
confidence: 99%
“…Xu et al 15 investigated the effect of MWCNTs on crystallization behavior of PTT and observed that MWCNTs provide more nucleation sites for crystallization. Wu et al 16 studied the mechanical and thermal properties of hydroxyl functionalized MWCNTs/acrylic acid grafted PTT composites and showed a significant enhancement in thermal and mechanical properties of PTT matrix due to the formation of ester bonds between -COOH groups of acrylic acid grafted PTT and -OH groups of MWCNTs.…”
Section: Introductionmentioning
confidence: 98%
“…Improved tensile modulus of functionalized SWCNT epoxy nanocomposites have been reported by Zhu et al . Enhancement in the thermal and mechanical properties of multi‐walled CNTs (MWCNTs)/poly(trimethylene terephthalate) (PTT) nanocomposites have been demonstrated by Wu et al in which MWCNTs are hydroxyl functionalized and PTT is acrylic acid grafted. Significant enhancements in the mechanical properties of functionalized SWCNT/poly(vinyl alcohol) (PVA) composites have been obtained by Liu et al .…”
Section: Introductionmentioning
confidence: 99%